STYLISTIC DA’WAH: The Study of Reprimand Verses in the Perspective of the Da’wah Method - Ircham, M; Halimah, Umi Saktie (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study discusses the method of da'wah using reprimand. The research was conducted to reveal the ways of reprimand in the verses of the Qur'an from the style of language (linguistic aspect). So far, the exploration of the method of da'wah in the Qur'an is still mostly focused on the substance of the verse. This study uses the method of stylistic analysis of the Qur'an which is descriptive, thematic, and inductive with a library approach. The results of this study are; first, the style of the Qur'an implies methods of admonishment in preaching and explains how these methods are applied. Second, the style of language in the reprimand is adjusted to the condition of the object and material of da'wah so that it can support the achievement of the mission of da'wah, namely changing the target of da'wah to a better condition. The methods and styles of language referred to are: (a) a gentle reprimand is delivered in an interrogative style for the target who makes mistakes unintentionally and is not fundamental; (b) a firm rebuke in an antithetical style for targets with fundamental errors and prior indications; and (c) a firm reprimand in a satire language style for socially positioned targets with a broad impact error.Keywords: Stylistic, Da'wah, Reprimand Verses